COVID-19, trust and solidarity in the EU - Cevat Giray Aksoy; Antonio Cabrales; Mathias Dolls; Lisa Windsteiger (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
We design and conduct large-scale surveys and experiments in eleven European countries to examine the effect of the COVID-19 pandemic on social trust, reciprocity, solidarity as well as institutional trust. Using incentivized outcome questions on trust and solidarity towards fellow citizens, people from other EU countries and non-EU countries, we assess the causal effect of priming respondents about the COVID-19 crisis. We find that respondents correctly believing that they live in an EU country with a below average COVID-19 incidence show higher levels of trust and reciprocity towards fellow citizens than respondents in the control group. In contrast, respondents who wrongly assume to live in a high incidence country reveal a lower level of reciprocity. For respondents who rightly believe that incidence is high in their country we find positive treatment effects on solidarity. Our study further establishes that the pandemic reduces trust in institutions, in particular for those respondents who (rightly) believe that their country's is strongly hit by COVID-19.
Keywords: D72; H51; H53; H55; O52; P52; 330; COVID-19; Europe; trust; reciprocity; solidarity; survey experiment